ICARE_08_12_029 ... : [Paysages, voyages, bateaux, divers] ... - Bénard], [Charles (NAKALA - https://nakala.fr (Huma-Num - CNRS), 2021)
Personnage chassant sur la banquise [Chasse au phoque] ... : Source: CNRS, UMR CReAAH, Archives, ICARE_PV0812029 ...